Analisis Bencana Longsor akibat Gempa bumi Cianjur 2022 dengan DInSAR - Brenda Arham; Adi Wibowo (P4W IPB, 2024)
Indonesia is a country with a high potential for disasters such as earthquakes, which usually cause changes in the shape/position of the earth's surface (deformation). The Cianjur area has a seismic vulnerability level value based on maximum ground acceleration, maximum intensity and earthquake return period. On Monday, November 21, 2022 at 13.21 WIB there was an earthquake with a magnitude of 5.6 M in the Cianjur area of West Java based on BMKG data, until November 22, 2022 there were 140 aftershocks with magnitudes of 1.2-4.2 and an average depth of approximately 10 km. As a result, causing subsidence, the purpose of this study is to determine the magnitude of subsidence in landslides due to the 2022 Cianjur earthquake using the DInSAR method. Vertical land subsidence (displacement data) due to the earthquake from DInSAR observations on displacement data, which ranged up to -101mm vertically with two soil types andosol and cambisol Overlay analysis of soil type and displacement data showed the highest area of displacement, found a match based on information circulating that Cugenang Sub-district is the most severely affected area (the existence of a new fault